Two new genera and two new species of Delphacidae (Hemiptera: Fulgoroidea) from China - Qin, Dao-Zheng; Zhang, Ya-Lin (Zootaxa, 2006)
Two new genera, Ramidelphax and Consociata, from southern China, are pr oposed within Delphacidae, based on th e new species Ramidelphax albistriata n. sp. (from Hainan and Guizhou Provinces, China ) and Consociata sinensis n. sp. (from Haina n Province, China). Because o f the presence of the post-tibal spur, the new genera should be place d in the tribe Delphacini.